Interrogating the Interplay between Media Teletechnology, AI and (Post)-truth through Derrida - Mandal, Tapan (Tattva journal of philosophy, 2024)
In 2016, the Oxford Dictionaries selected “post-truth” as the “Word of the Year” and defined it as “a term relating to or denoting circumstances in which objective facts are less influential in shaping public opinion than appeals to emotion and personal belief.”The 21st century has witnessed a radical transformation in the way information is disseminated and consumed by using technology based media power. The concept of truth, once considered a stable and objective foundation, has become malleable, elusive, and subject to manipulation. My paper tries to show how the media or teletechnology plays a pivotal role in shaping public perceptions and realities, post-truth. To navigate this complex landscape, we have to turn to the philosophy of Jacques Derrida and his portmanteau terms like artifactuality, actuvirtuality and teletechnology, which provide a compelling framework for understanding the interplay between truth, post-truth, and the media. Now the question arises whether Jacques Derrida is a catalyst of designing the idea of post-truth, although there are different registers of truths among which Derrida’s focus is on the truth in philosophy.Using the thoughts of Derrida in his filmed interviews Echographies of Television (with Bernard Stiegler) (Derrida and Stiegler2002) and Bernard Stiegler in his two volumes of Technics and Time (Stiegler1994, 2009), it can be shown how this information/power nexus is carved through a model of visual communication, gradually displacing and supplementing writing (while the ghost of writing surely continues to haunt, the way ghost of speech continued to haunt writing). I also intend to explain how the use of visual elements in information networks creates a new form of power and connection distinct from traditional print and analog forms of communication.